Metaanalisis Pengaruh Pendekatan STEM Terhadap Peningkatan Hasil Belajar IPA Peserta Didik - Fina Afriani Putri; Usmeldi; Asrizal (Jurnal Penelitian Pendidikan IPA, 2023)
Skills in the 21st century require students to have a highly cooperative attitude, be able to communicate well, be creative, and think at a high level. To apply these skills, the form of approach that can be applied is to use the STEM approach. This study has the objective of analyzing the effect of the STEM approach on improving students' natural science learning outcomes obtained by analyzing the effect size results. The research articles consist of 20 articles sourced from international and national journals. Effect Size analysis is based on the grouping of educational levels and student learning outcomes. It can be concluded that the STEM approach greatly influences the improvement of science learning outcomes for students at both elementary, junior high, and high school levels who are in the high category. And the STEM-based approach has a high influence on the three elements, especially on the knowledge element.